Masyarakat Pulau Di Utara Jawa Dan Pasang Surut Budayanya - Lucas Partanda Koestoro (Berkala Arkeologi, 1995)
Entering the twentieth century, there was a discussion on the nautical aspects of Indonesian culture. JC van Leur started to discuss the maritime nations in the "Mediterranean" region of Southeast Asia. Their lives are influenced by the sea, traders, and forging world trade networks. They are known as a nation of entrepreneurs who used to migrate, trade, and sail to various directions. Most of these communities were institutions of the Sriwijaya or Majapahit Kingdom.